Systematic evaluation of different types of graphene oxide in respect to variations in their in-plane modulus. (April 2017) - Feicht, Patrick; Siegel, Renée; Thurn, Herbert; Neubauer, Jens W.; Seuss, Maximilian; Szabó, Tamás; Talyzin, Alexandr V.; Halbig, Christian E.; Eigler, Siegfried; Kunz, Daniel A.; Fery, Andreas; Papastavrou, Georg; et al.
Abstract: Graphene oxide samples prepared in various laboratories following a diversity of synthesis protocols based on Brodie's (BGO) and Hummers/Offeman's (HGO) methods were compared in respect of their in-plane moduli. A simple wrinkling method allowed for a spatial resolution <1.5 μm by converting the wrinkling frequency. Quite surprisingly, a drastic variation of the in-plane moduli was found spanning the range from 600 GPa for the best BGO types, which is in the region of chemically derived graphene, all the way down to less than 200 GPa for HGO types. This would suggest that there are no two equal GO samples and GO should not be regarded a compound but rather a class of materials with very variable physical properties. While large differences between Brodie's and Hummers/Offeman's types might have been expected, even within the group of Hummers/Offeman's types pronounced differences are observed that, based on 13 C solid-state NMR, were related to over-functionalization versus over-oxidation. Graphical abstract: